Microbiome changes in the sponge Halichondria panicea along the Baltic Sea salinity gradient - Hoy, Philipp; Hassenrück, Christiane; Mittermayer-Schmittmann, Felix; Schmittmann, Lara; Jürgens, Klaus (Frontiers in Microbiology, 2026)
The Baltic Sea is characterized by a strong salinity gradient, which impacts the diversity and composition of free-living macro- and microorganisms. Much less is known about how host-associated microorganisms are affected by decreasing salinities. Marine sponges are known to harbor complex prokaryotic communities, relevant for the host’s health and functions. This raises the question of whether and how the sponge microbiomes are also subject to changes along the declining salinity of the South-western Baltic Sea. We analysed the microbiome of the dominating sponge, the marine demosponge Halichondria panicea, from high saline conditions (28.3 PSU) in the Kattegat to the Eastern limit of its distribution at lower salinities (11.4 PSU). We utilized a dual approach of 16S rRNA gene metabarcoding of sponge and seawater microbiomes, together with the absolute quantification of the total prokaryotic sponge community and the main bacterial symbiont, the alpha-proteobacterium Ca. Halichondribacter symbioticus (Ca. H.s.), by digital droplet PCR (ddPCR). All sponge microbiomes originating from the same location shared a highly similar prokaryotic community, clearly different from the surrounding water, and dominated by the known symbiont Ca. H.s. In addition, location-specific bacterial genera, enriched in the sponge microbiomes, were also found (e.g., Endozoicomonas, Shewanella, Ekhidna). Sponge microbiomes at the Eastern limit of the distribution of H. panicea, with the lowest salinity, showed a higher sponge microbiome diversity and an increased similarity between sponge and water microbiomes. Furthermore, at the lowest salinity, absolute bacterial abundance increased while Ca. H.s. remained at relatively stable absolute abundances. These observations were paired with a notable trend of decreasing body volume of sponge individuals, indicating lower fitness at the lowest salinities. We hypothesize that the observed shifts under low salinity conditions, with an increased occurrence of bacterial taxa from the surrounding water, reflect potential early signs of dysbiosis of the sponge microbiome, coinciding with the occurrence at their distribution limit. This study provides a first insight into the effects of changing salinity on the microbiome of H. panicea in the Baltic Sea, and on the shifts in sponge microbiomes that occur in environmental gradients such as the challenging environment of the Baltic Sea.